Moderate to Severe Acute Kidney Injury Leads to Worse Outcomes in Complex Thoracic Aortic Surgery - Guo, Ming Hao; Tran, Diem; Glineur, David; Al-Atassi, Talal; Boodhwani, Munir (The Annals of thoracic surgery, 2021)
The impact of acute kidney injury (AKI) in thoracic aortic surgery is not well defined. This study aimed to examine the impact of varying severity of AKI on in-hospital and long-term outcome in these patients. From 2004 to 2018, 1142 patients underwent thoracic aortic surgery at a single institution (University of Ottawa Heart Institute, Ottawa, Canada) and were stratified into 4 groups on the basis of the severity of postoperative AKI: no AKI (n = 705), Acute Kidney Injury Network (AKIN) stage 1 (n = 261), AKIN stage 2 (n = 72), and AKIN stage 3 (n = 104). Outcomes include in-hospital mortality, morbidity, and long-term survival. Multivariable logistic regression was used to identify independent predictors of AKI. Propensity score matching was performed to identify pairs of patients without postoperative AKI or with AKIN stage 1 AKI, as well as pairs of patients without postoperative AKI and those with AKIN stage 2 or higher AKI. Kaplan-Meier curves were plotted for late survival. In the propensity-matched cohort, patients with postoperative AKIN stage I AKI had worse in-hospital mortality but comparable long-term survival when compared with patients without postoperative AKI. Patients with AKIN stage 2 or higher AKI experienced significantly higher in-hospital mortality compared with patients without postoperative AKI (15.9% vs 4.6%; P < .01) and worse 8-year survival (65.9% ± 34.1% vs 80.1% ± 20.0%; P < .01). Moderate to severe AKI is a serious complication and is associated with significantly worse short- and long-term outcomes; targeting mild AKI with therapeutic intervention is an important step in improving patient outcomes.